A Case of Ileal Lipoma Protruded Beyond Anus - Fukuta, Y.; Oguchi, H.; Furihata, M.; Tashima, K.; Kitaichi, T.; Shimada, Y.; Otsuki, U.; Kuge, Y. (Nippon Daicho Komonbyo Gakkai Zasshi, 1992)
A 49 year old woman was referred to our hospital for tumor protrusion beyond anus. Under spinal anesthesia, the tumor was inserted through the anus. According to barium enema and colonofiberscopy examination, this tumor was present on the transverse colon, but it was not clear where this tumor developed. On laparotomy, actually this tumor developed on ileocaecal region and seemed like a malignancy so that the ileocaecal region and ascending colon was resected. On postoperative pathological study, it was understood that the tumor was benign lipoma developed on the ileum. Her postoperative course was very good and discharged 21 days after operation. Ileal tumor rarely protrudes beyond the anus.